2023
DOI: 10.1159/000533400
|View full text |Cite
|
Sign up to set email alerts
|

Telling Personal Narratives: Comparing Stories Told by 10-Year-Old Speakers of Cypriot Greek Dialect and of Standard Modern Greek

Elena Theodorou,
Ioannis Vogindroukas,
Eleni Giannakou
et al.

Abstract: Introduction: Cypriot Greek is the variety of Greek language used for oral communication by the Greek Cypriot people, while Standard Modern Greek is the official language. Cypriot Greek differs from Standard Modern Greek in various aspects, including lexicon, phonetics, phonology, morphosyntax and pragmatics. This study examines whether there are differences between children who are native speakers of the Cypriot Greek dialect and those who are native speakers of Standard Modern Greek in narrative measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Children Speaking Nonmainstream Dialects Accurate identification of language disorders is often difficult in children from culturally and linguistically diverse backgrounds, including children who speak nonmainstream dialects. As reported in this special issue, Theodorou et al [8] found group differences in syntactic ability when investigating the personal narratives of children speaking different varieties of Greek (Standard Modern Greek and Cypriot Greek dialect), with the children speaking Cypriot Greek dialect producing shorter sentences. These results are consistent with prior research in showing how dialect use may impact children's spontaneous language skills and highlight the importance of considering a child's dialect use when assessing language ability to avoid misidentification of language difference as language disorder.…”
Section: Tele-assessmentmentioning
confidence: 85%
See 2 more Smart Citations
“…Children Speaking Nonmainstream Dialects Accurate identification of language disorders is often difficult in children from culturally and linguistically diverse backgrounds, including children who speak nonmainstream dialects. As reported in this special issue, Theodorou et al [8] found group differences in syntactic ability when investigating the personal narratives of children speaking different varieties of Greek (Standard Modern Greek and Cypriot Greek dialect), with the children speaking Cypriot Greek dialect producing shorter sentences. These results are consistent with prior research in showing how dialect use may impact children's spontaneous language skills and highlight the importance of considering a child's dialect use when assessing language ability to avoid misidentification of language difference as language disorder.…”
Section: Tele-assessmentmentioning
confidence: 85%
“…Theodorou et al [8] investigated differences in personal narrative performance between groups of 10-yearold children who speak two varieties of the same language: Standard Modern Greek and Cypriot Greek Dialect. Children's personal narratives were analysed at both macrostructure (overall structure and inclusion of elements) and microstructure (verbal productivity, semantic diversity, and syntactic complexity) levels.…”
Section: An Overview Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation